Utility and Drawbacks of Chimeric Antigen Receptor T Cell (CAR-T) Therapy in Lung Cancer - Kandra, Prameela; Nandigama, Rajender; Eul, Bastian; Huber, Magdalena; Kobold, Sebastian; Seeger, Werner; Grimminger, Friedrich; Savai, Rajkumar (Frontiers in Immunology, 2022)
The present treatments for lung cancer include surgical resection, radiation, chemotherapy, targeted therapy, and immunotherapy. Despite advances in therapies, the prognosis of lung cancer has not been substantially improved in recent years. Chimeric antigen receptor (CAR)-T cell immunotherapy has attracted growing interest in the treatment of various malignancies. Despite CAR-T cell therapy emerging as a novel potential therapeutic option with promising results in refractory and relapsed leukemia, many challenges limit its therapeutic efficacy in solid tumors including lung cancer. In this landscape, studies have identified several obstacles to the effective use of CAR-T cell therapy including antigen heterogeneity, the immunosuppressive tumor microenvironment, and tumor penetration by CAR-T cells. Here, we review CAR-T cell design, present the results of CAR-T cell therapies in preclinical and clinical studies in lung cancer, describe existing challenges and toxicities, and discuss strategies to improve therapeutic efficacy of CAR-T cells.